1990
DOI: 10.1079/bjn19900035
|View full text |Cite
|
Sign up to set email alerts
|

Haematological studies on pre-menopausal Indian and Caucasian vegetarians compared with Caucasian omnivores

Abstract: Full blood counts, serum ferritin, vitamin B,, and folate, erythrocyte folate concentrations and nutrient intakes were estimated in twenty-three Indian vegetarian, twenty-two Caucasian omnivores and eighteen Caucasian vegetarian women aged 25-40 years. Energy and copper intakes were lower in the Indian women than in the Caucasians. Intakes of dietary fibre, vitamin C and folate were greater and the proportion of energy derived from fat was lower in the vegetarians than in the omnivores. Vitamin B,, and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 8 publications
(4 reference statements)
3
75
0
2
Order By: Relevance
“…Most have found vegetarians to have lower serum ferritin concentrations than omnivores [57,68,69,70]. Premenopausal women in the United States who consumed red meat had higher serum ferritin and hemoglobin concentrations, and lower total iron binding capacity compared with lacto-ovo vegetarians, or those consuming fish or poultry as their main protein source [64].…”
Section: Dietary Determinants Of Iron Status In Young Women Livingmentioning
confidence: 99%
“…Most have found vegetarians to have lower serum ferritin concentrations than omnivores [57,68,69,70]. Premenopausal women in the United States who consumed red meat had higher serum ferritin and hemoglobin concentrations, and lower total iron binding capacity compared with lacto-ovo vegetarians, or those consuming fish or poultry as their main protein source [64].…”
Section: Dietary Determinants Of Iron Status In Young Women Livingmentioning
confidence: 99%
“…It has been suggested that vegetarians could be at greater risk of ID [11], although some research results show that eliminating meat leads to higher intake of whole-grain and fortified cereals, legumes, nuts, seeds and dried fruit, and iron intake is often greater than in omnivores [12,13,14,15]. However, poorer iron status observed in the vegetarian diet may be due, at least partly, to lower iron bioavailability since non-haem iron (dairy products, eggs, all plant foods; absorbed 2-20%) is not absorbed as well as haem iron (meat, poultry, fish; absorbed 13-35%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Serum ferritin, the body's iron store, is strongly correlated with haem iron (Reddy and Sanders, 1990). Bioavailability of iron plays an important role in determining iron status.…”
Section: Meat and Satietymentioning
confidence: 99%